Developing blended learning the subject history of photography among photography student / Muhammad Asri Azuddin - Azuddin, Muhammad Asri (2015)
History is one of those subjects that have consistently suffered from negative views. In photography there also a History of Photography subject for photography students to learn. However, in formal studies about History of Photography students still learn through slideshow during class, taking notes and read some books. This conventional method however shows lack of interest among the students in classes, and this effect the result of the students in this subject. There are many aspects that already adapted and apply the advantages of it by using it to enhance or replace the previous method. The same the situation happen in the educational system todays where the technology have innovate many style of learning development. The objective of this study is to identify the lack of interest from the students towards this subject and to enhance the current method of learning in History of Photography subject to make it more interesting. A case study on History of Photography subject was employed by using methods of observation and interview towards students and lecturers. The finding shows that students and lecturers agreed if there are portable notes about this subject. These studies conclude that mobile learning is moderately new instrument in the pedagogical to support students and lecturers as they transverse the option available in the growing world.